2015
DOI: 10.1002/sim.6813
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of constrained randomization for the design and analysis of group‐randomized trials

Abstract: In group-randomized trials, a frequent practical limitation to adopting rigorous research designs is that only a small number of groups may be available, and therefore simple randomization cannot be relied upon to balance key group-level prognostic factors across the comparison arms. Constrained randomization is an allocation technique proposed for ensuring balance, and can be used together with a permutation test for randomization-based inference. However, several statistical issues have not been thoroughly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
154
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 72 publications
(161 citation statements)
references
References 24 publications
7
154
0
Order By: Relevance
“…This l 2 metric accommodates both continuous and categorical variables (dummy variables are used to represent a multicategory factor) and is invariant to linear transformations of covariates with the default choice of ω k . Two alternative balance metrics were developed with constrained randomization, but they were specifically designed to balance group‐level factors and may not accommodate continuous variables. To compare with the l 2 metric, we propose an l 1 analog Bfalse(l1false)=ktrueω˜kfalse|truex¯Tktruex¯Ckfalse|, where truex¯Tk,truex¯Ck and trueω˜k are defined similarly, and by default, trueω˜k is taken to be the inverse standard deviation of the group means.…”
Section: Motivating Examplesmentioning
confidence: 99%
“…This l 2 metric accommodates both continuous and categorical variables (dummy variables are used to represent a multicategory factor) and is invariant to linear transformations of covariates with the default choice of ω k . Two alternative balance metrics were developed with constrained randomization, but they were specifically designed to balance group‐level factors and may not accommodate continuous variables. To compare with the l 2 metric, we propose an l 1 analog Bfalse(l1false)=ktrueω˜kfalse|truex¯Tktruex¯Ckfalse|, where truex¯Tk,truex¯Ck and trueω˜k are defined similarly, and by default, trueω˜k is taken to be the inverse standard deviation of the group means.…”
Section: Motivating Examplesmentioning
confidence: 99%
“…16,17 Recently, Donner et al reported that ignoring matching can adversely affect other analyses, such as analyses that examine the relationship between a risk factor and an outcome; 18 for this reason, investigators considering pair-matching should consider small strata instead (e.g., strata of 4). Li et al 19 compared model-based and permutation methods in the context of constrained randomization adjusting for group-level covariates. They found that both the adjusted F-test and permutation test maintained the nominal size and had improved power under constrained randomization compared to simple randomization.…”
Section: Developments In the Analysis Of Parallel Group-randomized Trmentioning
confidence: 99%
“…They found that both the adjusted F-test and permutation test maintained the nominal size and had similar power, but cautioned that the randomization distribution must be calculated within the constrained randomization space to prevent inflating the type I error rate. 19 …”
Section: Developments In the Analysis Of Parallel Group-randomized Trmentioning
confidence: 99%
“…These were split into 2 strata for randomization: (1) Front Range and Eastern Plains and (2) mountains and Western Slope. Within each stratum, we used covariate constrained randomization 21,22 to achieve balanced study arms with respect to population and health resource characteristics. Variables included total population of the region, average county population, percentage at or below poverty level, median income, percentage white, percentage Hispanic, number of primary care physicians per 10,000 population, number of physician assistants/nurse practitioners per 10,000 population, unemployment rate, and number of uninsured adults aged 18 to 64 years old.…”
Section: Covariate Constrained Randomizationmentioning
confidence: 99%